2017
DOI: 10.12968/ijtr.2017.24.9.385
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation: Uptake and completion profile of patients with chronic obstructive pulmonary disease

Abstract: Background: Pulmonary rehabilitation (PR) is effective in the management of chronic obstructive pulmonary disease (COPD) patients. 33% of patients referred for PR do not start the programme.Aim: To examine the relationship between participation in outpatient PR and baseline measures of disease severity and psychosocial variables in COPD patients. Methods:In an observational study and prior to their first outpatient PR appointment, COPD patients completed outcome measures of depression (Brief Assessment Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, the proportion of individuals attending PR who have at least one other co-existing condition is between 51% and 96% meaning that motivation to engage in therapy ‘relating to the lungs’ may be overcome by the desire to attend to conditions not directly related to their respiratory disease. 7,11…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the proportion of individuals attending PR who have at least one other co-existing condition is between 51% and 96% meaning that motivation to engage in therapy ‘relating to the lungs’ may be overcome by the desire to attend to conditions not directly related to their respiratory disease. 7,11…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the proportion of individuals attending PR who have at least one other co-existing condition is between 51% and 96% meaning that motivation to engage in therapy 'relating to the lungs' may be overcome by the desire to attend to conditions not directly related to their respiratory disease. 7,11 Our inquiries through 'Breath Lab' and ethnographic research conducted through the Life of Breath project have indicated that there is a hesitation to pursue PR due to a lack of clarity as to what the programme involves and what this means for individuals. This empirical research has revealed that many of those consulted with a lung condition initially considered that PR comprised breathing techniques, while others were concerned with the probability of compulsory, intense exercise.…”
Section: Lung-centred Rehabilitation?mentioning
confidence: 99%
See 1 more Smart Citation